(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
This paper provides an overview of studies on closely related phonemes and their pronunciation. The phonological aspect of the pronunciation of sounds, the relationship between phonemes and their variants are considered. The author draws attention to the importance of correct pronunciation of sounds for understanding and coherence of speech. The features of the pronunciation of sounds in different languages and dialects are considered. The author draws attention to the need to teach correct pronunciation for people for whom this is a foreign language.